2021
DOI: 10.1016/j.bbi.2021.01.030
|View full text |Cite
|
Sign up to set email alerts
|

The three frontlines against COVID-19: Brain, Behavior, and Immunity

Abstract: The pandemic outbreak of coronavirus disease 2019 (COVID-19) is raising global anxiety and fear of both real and perceived health threat from the virus. Overwhelming evidence shows infected patients experiencing neuropsychiatric complications, suggesting that the “psychoneuroimmunity” model might be beneficial in understanding the impact of the virus. Therefore, this Special Issue on “Immunopsychiatry of COVID-19 Pandemic” was launched immediately after the pandemic was declared, with the first paper accepted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 97 publications
0
18
0
Order By: Relevance
“…[24][25][26] It has also been observed that the rate of suicide has not increased in China during the early stages of COVID-19, which is hypothesised to be due to an emphasis placed on community and family support mechanisms. 27,28 Japan, which historically has high suicide rates, reported a steady decrease in cross-national suicide rates up until 2020. 12 Immediately following the onset of the global COVID-19 pandemic, the Japanese federal government shut down the economy, including the closure of schools followed by social financial provisions.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] It has also been observed that the rate of suicide has not increased in China during the early stages of COVID-19, which is hypothesised to be due to an emphasis placed on community and family support mechanisms. 27,28 Japan, which historically has high suicide rates, reported a steady decrease in cross-national suicide rates up until 2020. 12 Immediately following the onset of the global COVID-19 pandemic, the Japanese federal government shut down the economy, including the closure of schools followed by social financial provisions.…”
Section: Discussionmentioning
confidence: 99%
“…We have reviewed the literature and have confirmed that SARS-CoV-2-infected patients are at high risk of developing neuropsychiatric complications, suggesting that the “psychoneuroimmunity” (interaction between psychological processes, nervous system and immunity) model may be helpful in understanding the effect of the virus [ 57 , 58 ]. During the COVID-19 pandemic, the most common psychiatric symptoms both in patients and health providers [ 59 ] were anxiety and mood disorders as well as suicidal thoughts [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the newly administered vaccinations and the currently available supportive treatments for COVID-19, a healthy lifestyle, including physical activity [ 69 ] and psychological interventions, have the potential to enhance the immunity against the virus and improve mental health during the COVID-19 pandemic [ 57 , 58 ]. Furthermore, Kinoshita et al used the snowball sampling method within a global network of telepsychiatry experts and found that the COVID-19 pandemic accelerated the promotion of telemedicine [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…A glimpse into the psychological reactions of the population to a global threat, evidenced fear/anxiety, insomnia, depression, anger, guilt, grief, loss at the beginning and frustration [3], PTSD, stigmatization later on, as well as the burnout, somatization of health care workers [4], the onset or aggravation of several psychological/psychiatric symptoms in some of the Covid patients, and the reactions of their family members, caregivers.…”
Section: International Challenges Of Psychiatric Care During the Covid-19 Pandemicmentioning
confidence: 99%
“…A gender analysis has revealed that younger women are more prone to develop especially anxiety, despite family support and resilience [3], due to an increase of household responsibilities, decrease of physical activity, the emergence of domestic hostility (violence, psychological and/or sexual abuse), due to more time spent together in close proximity. Two peaks of these psychological disturbances could be recorded: at outbreak and more severe later on in a specially vulnerable population: younger, single women, exposed to the infection [3].…”
Section: International Challenges Of Psychiatric Care During the Covid-19 Pandemicmentioning
confidence: 99%